ChemInform Abstract: An Overview and Future Perspectives of Aluminum Batteries. Issue 44 (13th October 2016) - Elia, Giuseppe Antonio; Marquardt, Krystan; Hoeppner, Katrin; Fantini, Sebastien; Lin, Rongying; Knipping, Etienne; Peters, Willi; Drillet, Jean‐Francois; Passerini, Stefano; Hahn, Robert
Abstract: Review: 184 refs.